Incorporating Peplau's Theory of Interpersonal Relations to Promote Holistic Communication Between Older Adults and Nursing Students. (March 2016) - Deane, William H.; Fain, James A.
With the increased life expectancy, older adults will interact with multiple health care providers to manage acute and chronic conditions. These interactions include nursing students who use various health care settings to meet the clinical practicum requirements of their programs. Nursing faculty are charged with facilitating students' learning throughout the program from basic human needs, to holistic communication, to advanced medical surgical concepts. Despite educating students on holistic communication, there remains a lack of a reliable framework to undertake the task of teaching holistic communication skills. Nursing students preparing to function as licensed practitioners need to develop appropriate knowledge to holistically care for older adults. The purpose of this article is to examine Hildegard Peplau's interpersonal relations theory as a framework to assist nursing students to understand holistic communication skills during their encounters with older adults. Peplau's theory provides nursing a useful set of three interlocking and oftentimes overlapping working phases for nurses' interaction with patients in the form of the nurse–patient relationship. Nursing education could adopt the three phases of Peplau's interpersonal relations theory to educate students on holistically communicating with older adults.